Studi Etnobotani Masyarakat Desa Sukolilo Kawasan Pegunungan Kendeng Pati Jawa Tengah - Irsyad, Muhammad Nur; Jumari, Jumari; Murningsih, Murningsih (Bioma : Berkala Ilmiah Biologi, 2013)
This research aims to reveal the types of plants used by communities for subsistence daily. This research conducted in the village of Kendeng Mountains region Sukolilo, Pati. Data collection conducted exploratory used a roaming method to inventory plant species. This method supported by ethnobotany participatory appraisal techniques consisting of: open-ended interview and participatory observation by the public as key informants. Inventory and interviews made in plant utilization category. Research showed that Sukolilo villagers still had a good knowledge about the diversity of plants and about plants their use in daily life. Inventory data showed that 208 species of plants used by the community, are grouped in categories: food (90 species), medicinal and traditional medicine (44 species), building materials (29 species), fuel wood (13 species), animal feed (11 species), craft materials and tools (8 species), fiber materials and rigging (3 species), and toxic materials (2 species).Â Keywords: ethnobotany, cultural value, karst areas, Kendeng mountains